Effect of aqueous and methanol extracts of Erythrina fusca Lour on DNA topoiso-merase II activity - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
DNA topoisomerase has been used as a primary target in the discovery of anticancer and antibiotics. In this study, the search for an inhibitor of DNA topoisomerases from Erythrina fusca Lour was carried out to evaluate a possible mechanism, since Erythrina has been used widely as an anticancer. Methanol and aqueous extracts from E. fusca leaves were prepared and analysed for their ability to stabilize the cleavable complex of mammalian DNA topoisomerase II. Results indicated that methanol extract was able to induce topoisomerase II-mediated DNA cleavage at the extract concentration of 0.1ng /ml. This was indicated by the presence of linear form of DNA substrate (pUC18), visualized on agarose gel electrophoresis. The aqueous extract, however, demonstrated the ability of cleaving pUC18 into the linear form, either in the presence and absence of DNA topoisomerase II. This activity was similar to that found on ribosome-inactivating proteins (RIPs). The RIPs activity on supercoiled pUC18 began to appear at a concentration of 0.05n/ill. The higher concentration of aqueous extract, the higher the RIPs activity. All activities found in E. fusca, might affect sinergistically as an anticancer.